Effects of intense training during and after pregnancy in top-level athletes - Kardel, K. R. (Scandinavian Journal of Medicine & Science in Sports, 2005)
This study investigates the effects of vigorous exercise during and after pregnancy in top competitive athletes. The hypothesis tested here is that training of sufficiently high volume during pregnancy can maintain initial fitness levels. A second hypothesis, that high-volume training during pregnancy in initially fit women does not pose a health risk for the mother or the fetus, was tested and found to hold in a prior report. The overall aim of the study was to define a safe training regime for the maintenance of fitness in top-level female athletes during pregnancy. Forty-one healthy athletes who had performed exercise regularly prior to conception were followed from gestational week 17 until 12 weeks postpartum while they performed standardized exercise programs. The subjects participated either in a high-volume exercise group (HEG, n520, 8.4 h week 1) or in a medium-volume exercise group (MEG, n521, 6 h week 1). The results show that well-trained women can benefit substantially from training at high volumes during an uncomplicated pregnancy. This can facilitate a rapid return to competitive athletics and physically active life after pregnancy. Guidelines for safe exercise by sufficiently fit women during pregnancy could be modeled on the high-volume exercise regime used here by the HEG.